Genome-wide miRNA expression profiling in Psathyrostachys huashanica reveals insights into the resistance response to barley yellow dwarf virus-GAV infection. (September 2022) - Shen, Chuan; Li, Xia
Abstract: Barley yellow dwarf virus-GAV (BYDV-GAV) is one of the most harmful viruses transmitted by aphids and can cause a severe yield loss on wheat, barley and oat. In previous study, Psathyrostachys huashanica ( P. huashanica ) was proved to be an effective resistance resource to BYDV-GAV. To investigate how miRNAs regulate gene expressions in defense to viral infection, we analyzed small RNA profiles in P. huashanica infected with BYDV-GAV at 3, 7 and 14 dpi (days post inoculation). Targets of differentially expressed miRNAs were predicted and associated analysis with mRNA sequencing was conducted. A total of 80 miRNAs were identified from 12 libraries, including 45 known miRNAs and 35 novel miRNAs. A series of differentially expressed miRNAs were identified at different infection stages. Gene ontology (GO) enrichment analysis showed that these target genes were enriched in regulation of biological process, response to stimulus, and catalytic activity. KEGG pathway enrichment analysis revealed that these target genes involved in a series of disease resistance-related pathways, including plant hormone signal transduction, and plant-pathogen interaction. The total 28 mRNA-miRNA pairs, including 10 known miRNAs and 4 novel miRNAs, were identified as being involved in viral resistance. RT-qPCR (Real-time quantitative polymerase chain reaction) verification analysis showed that most miRNAs and corresponding predicted target genes showed a negatively regulated pattern. Besides, 5' RLM-RACE assays were conducted for further validation. To our knowledge, our study is the first to describe miRNAs in P. huashanica and may offer a valuable database for additional miRNA research in other wild-type species relatives to cultivated crops. In addition, this study provides new insights into the underlying resistance molecular mechanisms upon viral infection. Highlights: It was the first time to report that sRNA sequencing of P. huashanica. 45 known miRNAs and 35 novel miRNAs were identified from sRNA sequencing. A combined analysis of RNA-seq and sRNA-seq was conducted to identify viral resistance-related mRNA-miRNA pairs. A series of potential targets were predicted and conducted by enrichment analysis.